TEACHING VOCABULARY IN EFL CLASSROOM : BY USING A SONG "TWINKLE TWINKLE LITTLE STAR" FOR YOUNG LEARNERS - MAYANG ISTIQOMAH (Journal of Language, Literature and Teaching, 2022)
Vocabulary is very important to understand and learn to support English learning activities. Without understanding vocabulary, it will be difficult to learn a language. Therefore, the introduction and teaching of English vocabulary is done early to children. The effort made by teachers to introduce and teach English vocabulary is through the media of a song. As a media tool, songs can be an alternative teaching solution that can be used by teachers to create effective and fun learning situations in the classroom. Songs can help students to more easily develop their English skills because there are various kinds of words and phrases to develop their vocabulary and pronounciation. The media song that can be used in teaching vocabulary for children is the song "Twinkle Twinkle Little Star". Learning in this English song media can be applied to children aged 5-12 years. In terms of teaching, many approaches can be applied according to the needs of students. humanism theory or approach plays an important role in educating children. This theory looks at how human relationships and is very important for the education of young learners and builds relationships between teachers and students and is centered on teaching. Whatever methodology the teacher uses to meet the needs of the learners, the humanistic approach will easily make young learners to remember, think, understand, and learn. Whatever methodology the teacher uses to meet the learners' needs, the humanistic approach will easily make young learners remember, think, understand, and learn. Thus, teachers have strategies that can be applied for young learners especially for children to be more efficient in learning English vocabulary.